ORIGIN OF THE LOUISVILLE RIDGE AND ITS RELATIONSHIP TO THE ELTANIN FRACTURE-ZONE SYSTEM - Watts, A; Weissel, J; Duncan, R; Larson, R (1988)
We have combined shipboard and Seasat altimeter derived data in an integrated geological and geophysical study of the Louisville Ridge; a 3500-km-long seamount chain extending from the Tonga trench to the Eltanin Fracture Zone. A break in the smooth trend of the ridge at latitude 37.5oS has been recognized in both bathymetric and altimetric data. The 40Ar-39Ar dating of rocks dredged either side of the break suggest that it is analogous to the bend in the Hawaiian-Emperor seamount chain. Although the general trend of the ridge can be fit by small circles about Pacific absolute motion poles determined from other seamount chains, the new bathymetric and age data allow us to refine Pacific absolute motion poles. -from Authors